Investigation on the Mass Loss of Bamboo Biochar by Thermogravimetric Analysis - Saedon, Mohd Zulkhairi; Jamellodin, Zalipah (Recent Trends in Civil Engineering and Built Environment, 2024)
In present era, sustainable materials are becoming more popular for structural materials applications, especially in Malaysia. On the other side, the choice of structural materials may have a substantial influence on the global climate, such as the greenhouse effect. Bamboo is one of the biomasses that can store carbon for a long time to prevent excessive greenhouse gas emissions to the environment. The purpose of this study is to use Thermogravimetric Analysis (TGA) to analyze the mass loss of bamboo biochar. The chemical content of biochar was analyzed using the data from supplier. The ungrounded bamboo biochar material was selected in this research. Firstly, the bamboo biochar has been burned in a furnace at various temperature of 500°C, 600°C and 700°C for 5 hours continuously. Thermogravimetric analysis testing is one of the methods that can characterize the material characterization through analysis of their decomposition pattern. The result of the TGA analysis indicates that 700°C biochar type was the highest mass loss during the testing. The results indicate that the bamboo biochar contain a variety of chemical composition. The findings of this study were highly significant and useful in developing initiatives to use a bamboo biochar as a benefit material to the environment.